Mismatch repair SNPs and thyroid cancer susceptibility: a potential role for the MSH6 rs1042821 (Gly39Glu) polymorphism - Santos, L. S. (2016)
Abstract of the Poster presented at the 3rd ESPT Conference (European Society of Pharmacogenomics and Personalised Therapy / European Society of Pharmacogenomics and Theranostics), 7-9 October 2015, Budapest.